Possible nechanisms of ethanol-mediated colorectal carcinogenesis: the role of Cytochrome P4502E1, Etheno-DNA Adducts, and the Anti-Apoptotic Protein Mcl-1 - Köhler, Bruno Christian; Scherr, Anna-Lena; Bruckner, Thomas; Gdynia, Georg; Jäger, Dirk; Mueller, Sebastian; Seitz, Helmut K. (Alcoholism, 2016)
Background Chronic alcohol consumption is a risk factor for colorectal cancer. The mechanisms by which ethanol (EtOH) exerts its carcinogenic effect on the colorectal mucosa are not clear and may include oxidative stress with the action of reactive oxygen species (ROS) generated through EtOH metabolism via cytochrome P4502E1 (CYP2E1) leading to carcinogenic etheno-DNA adducts. ROS may also induce apoptosis. However, the effect of chronic EtOH consumption on CYP2E1, etheno-DNA adducts as well as anti-apoptotic proteins in the colorectal mucosa of heavy drinkers without colorectal inflammation is still not known. Methods Rectal biopsies from 32 alcoholics (>60 g EtOH/d) and from 12 controls (<20 g EtOH/d) were histologically examined, and immunohistochemistry for CYP2E1 and etheno-DNA adducts was performed. Apoptosis (cleaved PARP) as well as anti-apoptotic proteins including Bcl-xL, Bcl-2, and Mcl-1 were immunohistochemically determined. Results No significant difference in mucosal CYP2E1 or etheno-DNA adducts was observed between alcoholics and control patients. However, CYP2E1 and etheno-DNA adducts correlated significantly when both groups were combined (p < 0.001). In addition, although apoptosis was found not to be significantly affected by EtOH, the anti-apoptotic protein Mcl-1, but neither Bcl-xL nor Bcl-2, was found to be significantly increased in heavy drinkers as compared to controls (p = 0.014). Conclusions Although colorectal CYP2E1 was not found to be significantly increased in alcoholics, CYP2E1 correlated overall with the level of etheno-DNA adducts in the colorectal mucosa, which identifies CYP2E1 as an important factor in colorectal carcinogenesis. Most importantly, however, is the up-regulation of the anti-apoptotic protein Mcl-1 in heavy drinkers counteracting apoptosis and possibly stimulating cancer development.